PERILAKU MAKAN DAN JENIS PAKAN ORANGUTAN(Pongo pygmaeus) DI YAYASAN INTERNATIONAL ANIMAL RESCUE INDONESIA (YIARI) KABUPATEN KETAPANG KALIMANTAN BARAT - Hadad, Abdullah A; Prayogo, Harri; Anwari, Sofyan (JURNAL HUTAN LESTARI, 2017)
Bornean orangutan (Pongo pygmaeus) is one of primate in Indonesia, the only species of great ape that could be found in Asia. Orangutan included in the IUCN list of endangered species category. The decreasing orangutan population is caused by various factors, however, the organization of International Animal Rescue Foundation Indonesia (YIARI) Ketapang gave much concerned and active to jointly maintain and conserve orangutans to avoid extinction. This study aims to determine feeding behavior and the food type for orangutan (Pongo pygmaeus) in the International Animal Rescue Foundation of Indonesia, Ketapang. Methods: Observations were made using the Focal Animal Sampling method. Based on the results and discussion, adult orangutans Joni, Pino and adolescents Gembar are more dominant in terms of mastery of the feed that is provided above the platform, while the child orangutan Vijai and Lisa are not too dominant. There are 15 kinds on food that is provided, and watermelon was the most favorite and also 17 kinds of food that the could get from the nature as the Ficus sp. was the most favorite. The most dominant orangutan feeding behavior is sitting, meal times ranging from 6:20 to 18:30 o'clock pm on the platform as the most dominant position.Keywords: Feeding behavior, Orangutans, West Borneo